Simplified follow-up of patients with mild chronic hepatitis C in areas with limited access to antiviral therapy. Issue 6 (June 2019) - Lens, Sabela; Torres, Ferran; Bonacci, Martin; Bartres, Concepció; Pocurull, Anna; Mariño, Zoe; Londoño, María-Carlota; Rodríguez-Tajes, Sergio; Forns, Xavier
Abstract: Background and aims: In some areas of the world, antiviral therapy for chronic hepatitis C (CHC) is not available for all patients. The optimal interval for liver stiffness measures (LSM) and noninvasive scores to assess fibrosis progression has not been studied. We evaluated the usefulness of consecutive LSM, APRI, FIB-4 and Forns scores to predict disease progression. Methods: Patients with CHC and at least two annual LSM within 3 years were followed for a minimum of 5 years. Noninvasive scores were assessed. Evolution of LSM and scores were expressed as change/year (Delta). Results: 623 non-cirrhotic patients were included. Median baseline LSM was 6.6 kPa (IQR 5.4–8.4). During a median follow-up of 6 years, 61(9.7%) patients developed cirrhosis. Baseline LSM ≥ F2 and Forns ≥ 6.9 were the main predictors of cirrhosis (C-index 0.97). The addition of Delta variables did not improve its prediction. In patients with mild fibrosis (F0-1), progression to ≥F2 occurred in 80 (23%) within the first 3 years. Baseline BMI ≥ 24 kg/m 2 and LSM ≥ 5.9 kPa were associated to progression. Conclusions: Baseline LSM and Forns are highly predictive of cirrhosis development. In patients with mild CHC, BMI < 24 and LSM < 5.9, the likelihood of progression is very low, allowing for a significant spacing of noninvasive assessments over time.